Autonomic instability, arrhythmia and visual impairment in a new presentation of MTFMT‐related mitochondrial disease. Issue 2 (8th December 2022) - Howard, Caoimhe; Dev‐Borman, Arundhati; Stokes, John; O'Rourke, Declan; Gillespie, Ciara; Twomey, Eilish; Knerr, Ina; Boruah, Ritma
Abstract: Mitochondrial methionyl‐tRNA formyltransferase (MTFMT) is required for the initiation of translation in mitochondria. Pathogenic variants in MTFMT have been described in association with clinical presentations with Leigh syndrome, as well with as multisystem involvement (particularly cardiac and ocular involvement). There is a spectrum of severity, but many reported presentations have been milder with a better prognosis than other pathogenic variants associated with Leigh syndrome. We describe the case of a 9‐year‐old boy homozygous for a pathogenic MTFMT variant (c.626C > T/p.Ser209Leu) who presented with hypertensive crisis on a background of hyperphagia and visual impairment. His clinical course was complicated by supraventricular tachycardia and severe autonomic instability, requiring intensive care unit admission. He also developed seizures, neurogenic bladder and bowel and had a markedly abnormal eye examination with bilateral optic atrophy. Magnetic resonance image brain showed abnormal high T2/fluid‐attenuated inversion recovery signal within the dorsal brainstem and in the right globus pallidus with some reduced diffusivity. Despite recovery from the acute neurological and cardiac manifestations, he has ongoing deficits in his gross motor skills and continues to have hyperphagia with rapid weight gain (approx. 20 kg in 2 years). Ophthalmic findings are persistent. This case expands the phenotype associated with MTFMT disease.